Plans as structured networks of hierarchically and temporally related case pieces - Macedo, Luís (2009)
This paper describes a representation of plan cases as a structured set of goals and actions. These goals and actions are the unit pieces that form a case. These case pieces are related each other by hierarchical and temporal links (explanations) forming a tree-like network. We give importance not just to explicit links, i.e., links between case pieces which are concretely known, but also to implicit ones, i.e., possibly unknown links between case pieces. Each case piece is explained by antecedent links and explains other case pieces by consequent links. The retrieval of a case piece is mainly guided by its links and by its surrounding case pieces. Our concept of case piece usefulness is briefly explained. We discuss the benefit of reusing and directly accessing small case pieces from multiple cases for improving the Case-Based Reasoning (CBR) systems’ capability and efficiency to solve problems. We explain the importance of stepwise refinement in plan cases and also the role that temporal representation can take in the meaningful and coherent construction of planning problem solutions. An application in musical composition domain is presented. We also show how a musical composition task can be treated as a planning task.